Determinant of Audit Fee - Cahyaningati, Retno; Miqdad, Muhammad; Kustono, Alwan Sri (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2021)
The credibility of financial reports is very important to increase the trust of parties outside the company. Several studies identified audit costing as providing credible evidence that a client's financial condition at risk demands more rigorous audit procedures. This study aims to identify whether Corporate Social Responsibility (CSR) and Good Corporate Governance (GCG) have an impact on audit costs. The research data are companies that have been registered in the Corporate Governance Perception Index (CGPI) for the period 2016 to 2018. The study population was 50 companies, while the research sample was 33 companies using a purposive sampling technique. The results of the regression analysis show that CSR does no effect on audit costs, the CSR program carried out and disclosed by the company is not included in the audit of the client's business by the auditor. Thus, the size of the CSR disclosure cannot affect audit costs. Meanwhile, GCG has a positive effect on audit costs. Companies with a good CGPI score can pay more audit fees because they have higher financial standards, so they choose the big four KAP which are more integrated and qualified.